Hungarian Monitoring, 2 February 1988 . [Magyar rádiófigyelő], 1988. február 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - BT meeting - West German-British summit in London - Bulgarian Party assembly - Contradictions in Soviet reforms - GDR releases political prisoners and detainees Domestic Affairs: - Silent protest at Romanian embassy building in Budapest - József Marjai at the Comecon meeting in Moscow - AIDS victim - Committee formed for organizing employment - Interview with Sándor Nagy, National Council of Trade Unions (SZOT) secretary - Conference of young economists - Hungarian environmental protection association formed Economy: - Hungary's interest payments - Chamber of Commerce secretary Péter Lőrincz on his Far Eastern trip Külpolitika: - Ülést tartott a BT - Nyugatnémet-angol csúcs Londonban - Bolgár pártértekezlet - Ellentmondások a szovjet reformokban - Politikai elítélteket és letartóztatottakat engedtek el az NDK-ban Belpolitika: - Néma tüntetés a budapesti román nagykövetség budapesti épületénél - Marjai József a moszkvai KGST találkozón - AIDS fertőzöttek - Foglalkoztatást szervező bizottság alakult - Interjú Nagy Sándor SZOT főtitkárral - Ifjú közgazdászok konferenciája - Magyar környezetvédelmi egyesület alakult Gazdaság: - Az ország kamatfizetési kötelezettségeinek alakulása - Lőrincze Péter a Gazdasági Kamara főtitkára számol be távol-keleti útjáról